Estudo comparativo de empatia entre estudantes universitários de profissões assistenciais e não assistenciais - Silva, Lucy Alves da (2012)
Submitted by Estagiário SPT BMHS (spt@fgv.br) on 2012-05-02T11:53:39Z No. of bitstreams: 1 000018127.pdf: 13573809 bytes, checksum: bf04556114e32f24f568007a612f152f (MD5) === Made available in DSpace on 2012-05-02T11:53:49Z (GMT). No. of bitstreams: 1 000018127.pdf: 13573809 bytes, checksum: bf04556114e32f24f568007a612f152f (MD5) Previous issue date: 1981 === The purpose of this work was to investigate the presence of different levels of empathy, among university students in graduation courses, for professions considered helpful or not, to population. It has been patent in the last years, the presence in therapists, of a high level of empathy which has brought about a healthy change in their patients. On the other hand, researches were made which proved that people needing help to solv personnal problems, have found great relief among non-therapist professionals. Based on these facts, two questions were brought forth: 19) Are the average grades among students in groups studing helpful professions higher than the ones in groups studing non-helpful professions? 29) Considering each profession separately do the avaerage grade s of the students in each course, show significant differences? To test null hypothesis the students had to take a Recognition Assessment-Empathy Inventory and grades obtained Were compared by means of a t test. As it is a preliminary study, where students took part, the results achieved should be regarded with caution and it is adviseable that the same test be given a second time, selecting a cross-section of experimented professionals. === Este trabalho teve por objetivo investigar a existência de diferentes níveis de empatia entre estudantes universitários de cursos preparatórios para profissões classificadas como assistenciais e não assistenciais. Nos últimos anos tem-se evidenciado a presença de um nível elevado de empatia nos terapeutas que provocam mudanças construtivas em seus clientes. Por outro lado, pesquisas levadas a efeito revelaram que pessoas necessitadas de ajuda para problemas pessoais, têm encontrado alivio para seus problemas junto a outros profissionais não terapeutas. Partindo-se destas evidências, duas questões foram levantadas: 19) a média dos alunos dos grupos de profissões assistenciais é maior do que a média dos alunos dos grupos de profissões não assistenciais? 29) Considerando-se cada profissão individualmente, a média dos alunos, em cada curso, apresenta diferenças significativas? Para testar as hipóteses nulas, os sujeitos foram submetidos ao Recognition Assessment-Empathy e as médias encontradas, comparadas através de um teste t. Por se tratar de um estudo preliminar, onde foram usados estudantes, os resultados encontrados devem ser encarados com as naturais reservas, recomendando-se que o mesmo seja replicado usando-se uma amostra de profissionais experientes.